Patterns for adaptive web applications - Koch, Nora (^p Datos electrónicos (1 archivo : 542 KB))
In this paper we present some patterns for adaptive Web applications, i.e. those Web applications that may change their behavior regarding the current user. These patterns refine the coarse grained personalization patterns in [Rossi 01], focusing on how adaptation can be implemented through the manipulation of links, and content and presentation of nodes. We first introduce the problem of building adaptive Web applications; next we introduce the patterns Adaptive Anchor Annotation, Anchor Selection, Sorting of Anchors and Conditional Fragments.